Top 10 Downloads from ACM's Digital Library. (Communications of the ACM, 2005)
This article presents links to several research papers, survey articles, and popular courses that can be downloaded from the Association of Computer Machinery's (ACM) digital library. Some of the papers listed out here are: "Architectures for a Temporal Workflow Management System," by Carlo Combi and Giuseppe Pozz; "Object-Oriented Programming: Tutorial," by Manuel Alfonseca; "Modeling Software Architectures in the Unified Modeling Language," by Nenad Medvidovic, David S. Rosenblum, David F. Redmiles, and Jason E. Robbins. Some of the most popular courses at the ACM Professional Development Centre for March 2005 are: Introduction to the Java Programming Language; Introduction to C#; Project Management: Initiation and Plan Launch; Using Decision and Looping Constructs With the Java Programming Language.